Herpetic Anterior Uveitis – Analysis of Presumed and PCR Proven Cases. (17th February 2019) - Neumann, Ron; Barequet, Dana; Rosenblatt, Amir; Amer, Radgonde; Ben-Arie-Weintrob, Yael; Hareuveni-Blum, Tamar; Vishnevskia-Dai, Vicktoria; Raskin, Eyal; Blumenfeld, Oren; Shulman, Shiri; Sanchez, Juan M.; Flores, Victor; et al.
ABSTRACT: Purpose : To describe the demographics and clinical characteristics of patients with herpetic anterior uveitis (HAU), and compare characteristics by pathogen, recurrence, and association to iris atrophy. Methods : Multicenter, retrospective study of AU patients diagnosed clinically and by polymerase chain reaction (PCR). Results : The study included 112 eyes in 109 patients: 54 (48.2%) HSV, 34 (30.4%) VZV, 2 (1.8%) CMV, and 22 (19.6%) unspecified diagnosis. HSV eyes, compared to VZV, had a higher recurrence rate, corneal involvement, KPs, iris atrophy, elevated IOP and posterior synechia ( p  < 0.05). VZV patients had more frequent immunomodulatory treatments and history of systemic herpetic disease ( p  < 0.05). Fifty-nine (52.7%) eyes had recurrent disease. Iris atrophy was associated with a higher prevalence of posterior synechia, dilated distorted pupil, and high IOP ( p  < 0.05). Conclusion : Different HAU-causing Herpesviridae produce common clinical findings; therefore, PCR should be used more often to confirm specific diagnosis. Iris atrophy was associated with more severe disease.